Arabidopsis α Aurora kinases function in formative cell division plane orientation - van Damme, Daniël (2011)
To establish three-dimensional structures/organs, plant cells continuously have to adapt the orientation of their division plane in a highly regulated manner. However, mechanisms underlying switches in division plane orientation remain elusive. Here, we characterize a viable double knockdown mutant in Arabidopsis thaliana group a Aurora (AUR) kinases, AUR1 and AUR2, (aur1-2 aur2-2), with a primary defect in lateral root formation and outgrowth. Mutant analysis revealed that aur1-2 aur2-2 lateral root primordia are built from randomly oriented cell divisions instead of distinct cell layers. This phenotype could be traced back to cytokinesis defects and misoriented cell plates during the initial anticlinal pericycle cell divisions that give rise to lateral root primordia. Complementation assays showed that the Arabidopsis a group Aurora kinases are functionally divergent from the single b group member AUR3 and that AUR1 functions in division plane orientation prior to cytokinesis. In addition to defective lateral root patterning, aur1-2 aur2-2 plants also show defects in orienting formative divisions during embryogenesis, divisions surrounding the main root stem cell niche, and divisions surrounding stomata formation. Taken together, our results put forward a central role for a Aurora kinases in regulating formative division plane orientation throughout development.